Spatio-Temporal Analysis of Crimes Against Women in UttarPradesh (2001-2018) - Sharma, Visha; Ishtiaque, Mohammad; Kumar, Dimple (National Geographical Journal of India, 2022)
The crime against women is a subject of great concern globally but in the Indian context it much alarming especially in Uttar Pradesh. According to the National Crime Record Bureau (NCRB) report 2018, 378277 cases of crime against women were reported in India up from 359849 in 2017 and Uttar Pradesh topped the list with 59445 cases. The present paper is an attempt to show a Spatio-temporal analysis of crimes against women in Uttar Pradesh. The analysis is based on the secondary data that was collected from the National Crime Record Bureau (NCRB)and the Census of India. The main objective of this research is to show the trend and patterns of crimes against women in the state. Correlation technique has been used to analyse the data and maps have been prepared based on the calculated results. To perform the correlation several demographic variables have been selected to understand the degree of crimes against women. The results of the research work differed for variables as some of them have a strong positive relationship while others have negative. It is to be noted that sex-ratio and literacy the variables have a strong positive correlation with the crimes in the majority of the districts of the study area